Student Learning Independence Through Flipped Classroom In Inclusive Elementary School - Khafidhotul Khasanah; Farid Ahmadi; Endang Susilaningsih (Universitas Negeri Semarang, 2022)
This study aims to describe the learning independence of fifth grade students of Inclusive Elementary School through flipped classroom learning model. The research method used is qualitative method. Data were collected using triangulation techniques and the results of the study put more emphasis on the results of data generalizations obtained from the results of questionnaires, observations, interviews, and field notes. Based on the research results, it can be concluded that 3 out of 16 learners (19%) have high learning independence, 7 out of 16 learners (44%) have moderate learning independence, and 3 out of 17 learners (19%) have low independence. Flipped classroom is quite effective to support the implementation of differentiated learning in inclusive classrooms since it helps teachers in dividing the time to provide differentiated learning for students with special needs while regular learners carry out deeper learning via activities. Providing learning tasks at home also helps to be efficient in teaching material in class and can increase parental involvement to actively help their children carry out independent learning tasks in pre-class activities. This is expected to increase students' learning independence in inclusive elementary school. .